Capturing solar energy - Rawlings, Rosemary (Chartered Institution of Building Services Engineers, 2009)
This publication provides an overview of the available domestic and non-domestic solar system solutions, technologies and applications. It is principally directed at the designers of building services and others who may not be aware of the many solar options available and their possibilities. It will also help clients, building owners and facilities managers to understand the possibilities of using solar technology in their buildings. Solar radiation is one of the most versatile and plentiful sources of renewable energy at our disposal. It can be captured and used both directly and indirectly, and can provide a significant contribution to the reduction of carbon emissions from fossil fuels. Solar solutions offer additional opportunities to meet the requirements of planning policies and building regulations. This publication considers the technologies available for capturing solar energy and the application of these technologies. It also highlights some of the main design and installation issues and commissioning and maintenance requirements, and provides information on regulations and costs. In order to encourage the inclusion of solar applications into building design the UK government has been, and is, providing a range of incentives and these are summarised. -- Provided by publisher.
Keywords: Solar energy.; elektronické knihy; electronic books